Veganism against Patriarchy: Non-Human Animal and Animalized Violence in The Vegetarian - Schrijvers, Deborah (FRAME, Journal of Literary Studies, 2026)
In this article, Deborah Schrijvers examines the way in which veganism is portrayed as silent activism against violence targeting women and non-human animals in the South-Korean novel The Vegetarian. Through the concepts of the “animal gaze” by Jacques Derrida and the “face” by Emmanuel Levinas, she argues that the female protagonist recognizes her own suffering under patriarchal structures through that of non-human animals. As such, she acknowledges her interrelated precarity as woman and animalized other, effectively represented through her silence throughout the novel. By employing an ecofeminist perspective on the gendering of meateating, Schrijvers investigates how veganism is made to serve as an interrelated liberation of women and non-human animals.